Research and Comparison of Distribution Automation Communication Mode Based on a Typical Case - Feng Wang; Xiaoping Si; Fang Zhao; Zhaohui Li; Haiyong Luo (Dianxin kexue)
As an important part of the distribution automation system， the communication network is a necessary toolfor the control center transmitting and collecting data of remote terminals and controlling it. Hence， the networkplays an important role in the composition and function implementation of the system. Distribution automationcommunication modes contain optical fiber communication， power line communication， and wireless communicationand so on. Different communication modes have big influence on the real time， reliability and effectiveness of thesystem， and also there is a big difference between the construction and maintenance cost. Through designing thecommunication network in a switching station in Shanghai， the difference among optical fiber communication， powerline communication and wireless communication was analyzed and compared， which provided a reference for theconstruction of the distribution automation communication network.